2020
DOI: 10.1186/s12904-020-00675-1
|View full text |Cite
|
Sign up to set email alerts
|

Talking about death and dying in a hospital setting - a qualitative study of the wishes for end-of-life conversations from the perspective of patients and spouses

Abstract: Background End-of-life (EOL) conversations are highly important for patients living with life-threatening diseases and for their relatives. Talking about the EOL is associated with reduced costs and better quality of care in the final weeks of life. However, there is therefore a need for further clarification of the actual wishes of patients and their relatives concerning EOL conversations in an acute hospital setting. Aim The purpose of this study was to explore the wishes of patients and their relatives wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…In accordance, a qualitative study including patients with haematological malignancy found that patients expected the HCPs to have an open mind towards end-of-life care (Bergenholtz et al, 2020). However, in contrast it, was found that the wish to talk about end-of-life among patients and caregivers differed widely, which necessitates the development of conversational tools facilitating dialogue (Bergenholtz et al, 2020). We found the preparatory material assisted different wishes between participants for preferred information regarding end of life; it was helpful and experienced as trustful by participants.…”
Section: Equality In Communication In An Unequal Relationmentioning
confidence: 87%
See 1 more Smart Citation
“…In accordance, a qualitative study including patients with haematological malignancy found that patients expected the HCPs to have an open mind towards end-of-life care (Bergenholtz et al, 2020). However, in contrast it, was found that the wish to talk about end-of-life among patients and caregivers differed widely, which necessitates the development of conversational tools facilitating dialogue (Bergenholtz et al, 2020). We found the preparatory material assisted different wishes between participants for preferred information regarding end of life; it was helpful and experienced as trustful by participants.…”
Section: Equality In Communication In An Unequal Relationmentioning
confidence: 87%
“…Additionally, the participants of this study described anticipating the HCPs bringing up topics of end of life. In accordance, a qualitative study including patients with haematological malignancy found that patients expected the HCPs to have an open mind towards end-of-life care (Bergenholtz et al, 2020). However, in contrast it, was found that the wish to talk about end-of-life among patients and caregivers differed widely, which necessitates the development of conversational tools facilitating dialogue (Bergenholtz et al, 2020).…”
Section: Equality In Communication In An Unequal Relationmentioning
confidence: 99%
“…Patient involvement, including shared decision-making, has become a key topic in healthcare, and this also includes patient involvement (if possible) in decisions regarding the level of life-sustaining treatment. However, this warrants an individual approach to ensure that the level of involvement is in accordance with the patient’s wishes [ 43 , 44 ]. The results from this study present current practice and will hopefully promote further interest in patient involvement in shared decision-making about the level of life-sustaining treatment.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has also created an unprecedented number of fast-tracked research, which highlights the need to test and share examples of best practice as soon as they become available. A follow-up survey is underway to remedy some of the sample bias [49,50] and to gauge real-time data about how COVID-19 has affected people's attitudes towards, and engagement with, EoLC planning.…”
Section: The Impact Of Covid-19mentioning
confidence: 99%